Access to evidence: the "discloruse scheme" of the damages directive - Marcos, Francisco (IE University, 2022)
Like with other harms for which compensation may be sought, evidence of harmful antitrust wrongs is essential for the success of damages' claims. In the context of most antitrust infringements, the information asymmetry between the parties and the difficulties faced by claimants to access probative evidence in support of their actions is severe. In the European Union, the tools available to the parties for discovery and access to evidence in adversarial processes for antitrust damages claims are governed by national law, but the rules in force in Member States should respect the principle of effectiveness. To help filling the information vacuum of the parties, the Damages Directive introduced a novel 'disclosure scheme', designed to ease the access to evidence necessary by both parties to prove their claims or counterclaims. This chapter examines how Member States have implemented the Directive in this regard and the common problems seemingly faced by them. It also looks at the early experience of the use and functioning of the ‘disclosure scheme’. In addition, alternative tools for obtaining evidence that might be used in connection with antitrust damages proceedings are also analyzed, particularly access to the files of Competition Authorities for follow-on claims.
Keywords: Evidence; Damages' claims; Discovery; Confidentiality; NCA; European Commission; Private enforcement; Compensation; 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas